The Study of Antibacterial Properties of Anbarnasara Smoke on Multi-Drug Resistant Bacteria Isolated From Urinary Infection in Pregnant Women - Afsaneh Molamirzaei (Alborz University of Medical Sciences, 2020)
Background: Using smoke from burning donkey dung has been popular in the treatment of many diseases in Iran. Objective: This study aimed to investigating the antimicrobial properties of donkey dung smoke on multi-drug resistant (MDR) bacteria isolated from urinary infection. Materials and Methods: First, 300 and 200 urine samples were collected from pregnant and non-pregnant women in Isfahan, Iran. Then in each group, 100 bacterial isolates including Escherichia coli, Klebsiella pneumonia, Proteus vulgaris, Staphylococcus epidermidis, Staphylococcus aureus, Pseudomonas aeruginosa, and Staphylococcus saprophyticus were isolated. Antibiotic resistant protocol was determined by antibiogram test. Donkey dung was sterilized, disintegrated, and heated. The smokes were concentrated in n-hexane solvent (65%) and were collected after evaporation of the solvent. Finally, the antibacterial activities of the concentrations of 0.25, 0.5 and 1 mg/mL of the smokes were detected using disk diffusion and macrodilution methods. Results: The most abundant MDR isolates causing urinary infections in pregnant and non-pregnant women was Escherichia coli. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of donkey dung smoke on MDR isolates from pregnant women were 0.25 mg/mL and 0.5 mg/mL, respectively. In the case of MDR isolates in non-pregnant women, the MIC of the smoke on Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus was 0.25 mg/mL, and the MBC on these isolates was 0.5 mg/mL. Conclusion: The smokes from donkey dung investigated in the present study have suitable potentials for controlling the infections after In vivo analysis.